A narrow range of transcript-error rates across the Tree of Life - Li, Weiyi; Baehr, Stephan; Marasco, Michelle; Reyes, Lauren; Brister, Danielle; Pikaard, Craig S.; Gout, Jean-Francois; Vermulst, Marc; Lynch, Michael (Science advances, 2025)
Although transcript-error rates are markedly higher than DNA-level mutation rates, a broad perspective on the degree to which they diverge across lineages remains to be developed. Using modified rolling-circle sequencing, we found a narrow range of transcript-error rates across the Tree of Life, with little evidence supporting local control of error rates associated with gene expression levels. Most errors result in missense changes if translated, and, as with a fraction of nonsense errors, these are underrepresented relative to random expectations, suggesting the existence of mechanisms for purging some such errors. To understand how natural selection and random genetic drift might shape transcript-error rates, we present a model based on cell biology and population genetics. However, while this framework helps understand the evolution of this highly conserved trait, as currently structured, it explains only 20% of the variation in the data, suggesting a need for further theoretical work in this area. Genome-wide analyses of transcript errors using a modified rolling-circle sequencing method reveal a narrow range of error rates.